PENERAPAN TEKNIK RELAKSASI NAPAS DALAM TERHADAP INTENSITAS NYERI PADA PASIEN POST OPERASI SECTIO CAESAREA (SC) - Nain Dhatun Nur Rokhmah; Devy Dwi Syavitri; Fajar Cahyono; Mugi Rahayu; Sri Maliana; Wahyuningsih Wahyuningsih (SINERGI : Jurnal Riset Ilmiah, 2026)
Pain is a common problem experienced by patients after undergoing Caesarean Section (CS) due to surgical incision of the abdominal wall and uterus. Poorly managed postoperative pain may limit mobilization, disturb rest, and delay maternal recovery. One non-pharmacological intervention that can be applied to reduce pain intensity is the deep breathing relaxation technique. This mini research aimed to describe pain intensity in post Caesarean Section patients after the application of deep breathing relaxation. This study used a case study approach involving five patients on the first day after Caesarean Section surgery. Pain assessment was conducted using the Numeric Rating Scale (NRS) before and after the intervention over three days of care. The results showed that before the intervention, all patients experienced moderate to severe pain with pain scores ranging from 5 to 8. After the implementation of deep breathing relaxation for 3x24 hours, a gradual reduction in pain intensity was observed in all patients. On the third day of evaluation, pain scores decreased to 2-3, which were categorized as mild pain. Patients appeared more relaxed, facial expressions of pain were reduced, and they were able to perform light mobilization more comfortably. In conclusion, deep breathing relaxation is effective as a non-pharmacological nursing intervention to help reduce pain intensity in post Caesarean Section patients